Mafhum Zawaj al-Misyar wa Shuwaruhu Baina al-Fiqh wa al-Qanun - Abd al-Salam Humud Ghalib al-Ansi; Abdul Mukit; A. Ubaedillah; Badrut Tamam; Syibawaih Syibawaih (Syura: Journal of Law, 2023)
This study aims to investigate misyar marriage from a theoretical and practical perspective, which the jurists, predecessors and successors, have debated between those who permit it and those who deny it, who are content with their evidence and are happy with their parties. We learned that all claims in religion must be presented with conclusive evidence and clear proofs in order for them to come close to the truth and correctness that God has guided to those of understanding. Based on the above, the researchers presented questions on this topic, which are: 1) How is the concept of misyar marriage? And 2) how he photographed it. The method used is the descriptive method in library studies, where the researchers followed the secondary and additional sources by reading, looking, and analyzing them, then described them qualitatively until they concluded the conclusion from them. The result reached is what can be considered as permissibility subject to controls and only when necessary. As is well known, this marriage is not the legitimate and required marriage that achieves its purposes, but the situation that the matter has reached is estimated and the woman is made to go ahead with that and give up part of her right, with warning and attention. With conditions.